TOWARDS COMPREHENSIVE SOCIAL CHANGE: A LEGAL ANTHROPOLOGICAL PERSPECTIVE IN HANDLING THE ISSUES OF SEXUAL HARASSMENT - Dinanti, Dinda (Fakultas Ilmu Budaya, Universitas Brawijaya, 2024)
This research will explore the legal anthropology approach in responding to issues regarding sexual harassment, with the aim of achieving comprehensive social change. Sexual harassment, in this case, has become a complex problem and requires a holistic solution, not only in the form of law enforcement. In this case, it emphasizes the integration of a specific legal anthropology perspective that understands the culture and social context into efforts to handle the issue of sexual harassment. The research stage will include a comprehensive literature review regarding concepts in legal anthropology, such as legal pluralism, legal awareness and restorative justice. Next, it will analyze how this approach can be applied in handling sexual harassment cases by considering aspects of culture, gender and power. Law is seen as a means of maintaining societal values, so legal values are basically institutionalized societal values. A legal anthropology perspective on the issue of sexual harassment includes identifying cultural contexts that encourage understanding of different interpretations and applications of law in artistic contexts. There are seven main factors related to sexual harassment, such as gender inequality and low economic conditions. Holistic treatment is needed by integrating traditional positive values, transforming cultural norms, utilizing traditional conflict resolution mechanisms and empowering the role of traditional leaders and leaders. The feminist perspective also emphasizes the importance of gender awareness and equality.